Torsion of a Wandering Spleen Involving the Pancreatic Tail and Splenic Flexure and Isolated Left-Sided Portal Hypertension due to Chronic Splenic Vein Thrombosis - Kachare, Manohar; Jaisinghani, Pooja (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Wandering spleen is a rare entity, wherein the spleen is attached only by an elongated vascular pedicle, predisposing it to complications like hilar torsion, infarction, rupture, etc. Pancreatic volvulus is another very rare anomaly, with isolated case reports described in association with wandering spleen. The presentation varies from asymptomatic lump (stimulating a mass) to acute abdomen (due to torsion). We present a case of 26-year-old female patient who complained of pain in abdomen, and was radiologically diagnosed and surgically confirmed to have a torsion of wandering spleen with involvement of pancreatic tail and splenic flexure. Few cases with associated finding of gastric volvulus and sigmoid volvulus have been described previously. Involvement of descending colon in a 9-year-old child has been reported. However, to the authors' knowledge, this is the first case report describing the combination of wandering spleen with splenic flexure and pancreatic tail involvement in an adult.
Keywords: wandering spleen; torsion; volvulus; CT; ultrasound